The architecture of John Russell Pope. Volume three / with introductory text by Royal Cortissoz. - Pope, John Russell, 1874-1937. (Tufts University. Tisch Library., 2020)
1 online resource : illustrations.; Tisch In-House Digitization 2020-02-04; Volume 3 only